2019
DOI: 10.1088/1475-7516/2019/07/037
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the sound of dark sector interactions with gravitational wave standard sirens

Abstract: We consider two stable Interacting Dark Matter -Dark Energy models and confront them against current Cosmic Microwave Background data from the Planck satellite. We then generate luminosity distance measurements from O(10 3 ) mock Gravitational Wave events matching the expected sensitivity of the proposed Einstein Telescope. We use these to forecast how the addition of Gravitational Wave standard sirens data can improve current limits on the Dark Matter -Dark Energy coupling strength (ξ). We find that the addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 328 publications
(405 reference statements)
0
55
0
2
Order By: Relevance
“…33 −0.33 , both at 95% CL, which are indeed not that far from those obtained within the ΛCDM cosmology, M ν < 0.12 eV and N eff = 3.00 +0. 36 −0.35 for the same data combination. Current cosmological observations are therefore powerful enough to disentangle the physical effects associated to the different dark sector components, i.e.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…33 −0.33 , both at 95% CL, which are indeed not that far from those obtained within the ΛCDM cosmology, M ν < 0.12 eV and N eff = 3.00 +0. 36 −0.35 for the same data combination. Current cosmological observations are therefore powerful enough to disentangle the physical effects associated to the different dark sector components, i.e.…”
Section: Discussionmentioning
confidence: 94%
“…33 −0.33 , both at 95% CL, which are close to those obtained within the ΛCDM cosmology, Mν < 0.12 eV and N eff = 3.00 +0. 36 −0.35 for the same data combination.…”
mentioning
confidence: 94%
“…It has been found that the presence of an interaction in the dark sector could successfully reconcile the long lasting cosmic coincidence problem [3,4,5,6,7]. Following this, a number of investigations in the context of interacting DE -DM models were performed by many investigators [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] (also see two review articles in this direction [44,45]). An interesting outcome from the interaction is that, it could naturally explain the phantom dark energy equation-ofstate [46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…These have focused on the DE equation of state (EoS) w x and its time evolution, or on models of modified gravity that can account for DE, by studying imprints on the background evolution and on the late-time growth of structure (see e.g. Ishak et al 2006;Mena et al 2006;De Felice et al 2008;Giannantonio et al 2010;Lombriser et al 2012;Martinelli et al 2012;Hu et al 2016;Nunes et al 2017a,b;Renk et al 2017;Peirone et al 2018;Vagnozzi et al 2018;Du et al 2019;Yang et al 2019a), and finally on the propagation of astrophysical gravitational waves (see e.g. Creminelli & Vernizzi 2017;Sakstein & Jain 2017;Ezquiaga & Zumalacárregui 2017;Boran et al 2018;Baker et al 2017;Visinelli et al 2018;Crisostomi & Koyama 2018;Langlois et al 2018;Ezquiaga & Zumalacárregui 2018;.…”
Section: Introductionmentioning
confidence: 99%